2022
DOI: 10.1037/hea0001143
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorder (PTSD), sleep, and cardiovascular disease risk: A mechanism-focused narrative review.

Abstract: Objective: Growing longitudinal research has demonstrated that posttraumatic stress disorder (PTSD) precedes and predicts the onset of cardiovascular disease (CVD), and a number of physiological (e.g., dysregulation of the hypothalamic-pituitary-adrenal axis and autonomic nervous system, chronic systemic inflammation) and behavioral (e.g., physical inactivity, smoking, poor diet) factors might underlie this association. In this narrative review, we focus on sleep as a modifiable risk factor linking PTSD with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 118 publications
(136 reference statements)
1
12
0
Order By: Relevance
“…51 In a recent study of young adults, individuals with insomnia, including frequent nighttime waking, displayed a lower wake-to-sleep reduction in heart rate than those without insomnia. 52 Insomnia-associated alterations in the renin-aldosterone-angiotensin system, which is promotes atrial remodeling, have also been proposed, 53,54 along with inflammation, endocrinological and/or adrenergic dysfunction, 55 all of which are well-described potential mediators of AF risk. [56][57][58] Other data from the UK Biobank showed that genetically-predicted insomnia is associated with a 13% higher risk of AF, and risk for eight other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…51 In a recent study of young adults, individuals with insomnia, including frequent nighttime waking, displayed a lower wake-to-sleep reduction in heart rate than those without insomnia. 52 Insomnia-associated alterations in the renin-aldosterone-angiotensin system, which is promotes atrial remodeling, have also been proposed, 53,54 along with inflammation, endocrinological and/or adrenergic dysfunction, 55 all of which are well-described potential mediators of AF risk. [56][57][58] Other data from the UK Biobank showed that genetically-predicted insomnia is associated with a 13% higher risk of AF, and risk for eight other cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Disrupted sleep may also be a key hyperarousal PTSD symptom and potential moderator of the development and growth of MetC. Sleep quality has been associated with many MetC and is a common outcome of social isolation (see Meinhausen et al, 2022 for a review). Therefore, poor sleep quality and quantity may also be a key mechanism through which hyperarousal symptoms overactivate physiological stress responses through the HPA axis and sympathetic adrenal medullary system, leading to poorer mental and physical health symptoms and, potentially, systemic illness following psychological trauma.…”
Section: Effect Of Hyperarousal and Emotional Numbing Symptoms On Metcmentioning
confidence: 99%
“…Our field has identified novel behavioral and psychosocial risk and prognostic factors for multiple CVD presentations and plausible mechanisms through which these factors could influence the development and course of CVD. Examples that reflect the ongoing evolution and expansion of the field’s focus are the articles in this issue on posttraumatic stress disorder and symptoms (Eisenberg et al, 2022; Krantz et al, 2022; Meinhausen et al, 2022), poor sleep quality and quantity (Meinhausen et al, 2022; Park & Kim, 2022), attention-deficit/hyperactivity disorder (Xu et al, 2022), and behavioral flexibility (Habibović et al, 2022)—all of which identify candidate treatment targets for future intervention studies.…”
Section: We Need To Refocus Our Science On the Clinical Research And ...mentioning
confidence: 99%